Sodium butyrate promotes synthesis of testosterone and meiosis of hyperuricemic male mice - Jiaojiao Qi; Yu Sun; Zeqing Chen; Ruipeng Gao; Miao Song; Tong Zou; Xuelin Gong; Shuang Wang; Qing Zhang; Chengyang Liu; Shichao Xing (Scientific Reports)
Abstract Hyperuricemia (HUA) impaires spermatogenesis. This study was carried out, aiming to determine whether butyric acid (NaB) avoids the HUA-induced decline of sperm quality HUA mice were developed through intra-peritoneal injection of the potassium oxalate combined with intragastric uric acid (UA) and by tube feeding 300 mg·kg-1·d-1NaB. The effect of NaB on the reproduction of HUA male mice was determined by measuring sperm count, sperm motility and testosterone content. In addition, TM3 and GC-2 cells were treated with a solution containing 30 mg/dl UA and 1mM NaB. The effects of NaB on the sperm quality were evaluated with the expression level of the genes involving in LH/cAMP/PKA signaling pathway and meiosis, and that encoding OPRL1 receptor protein. Results showed that NaB improved sperm count, sperm motility, testosterone synthesis, and impaired spermatocyte meiosis via HUA. In addition, in vitro analysis showed that NaB activated the LH/cAMP/PKA signaling pathway of TM3 cells, promoted the synthesis of testosterone, up-regulated the content of pain-sensitive peptide receptor (OPRL1) on the surface of GC-2 cells, and promoted meiosis. NaB also promoted the utilization of ATP by GC-2 cells. We illustrated a close relationship between HUA and spermatogenesis defects. NaB-promoted the expression of the genes functioning in testis meiosis, and the testosterone content may aid to improving spermatogenesis quality.